MARKETING STRATEGY AT INDO NATURAL FARM SUKABUMI EDUTOURISM - Firman, Arief; Nurjanah, Siti (SEMNASTERA (Seminar Nasional Teknologi dan Riset Terapan), 2024)
Abstrack This research aims to determine the implementation of the marketing strategy at Eduwisata Indo Natural Farm Sukabumi in increasing ticket sales as well as finding out the obstacles and solutions in implementing the marketing strategy. This research uses descriptive research by direct observation of the company, interviews with company owners and describing the data together with the situation that occurred at Eduwisata Indo Natural Farm Sukabumi. The results of this research show that Indo Natural Farm Sukabumi in implementing marketing strategies using STP, namely Market Segmentation (segmenting), Target Market (Targeting) and Market Position (Positioning), is quite optimal. Eduwisata Indo Natural Farm applies market segmentation based on geography, with the main focus on the Sukabumi City and Regency areas. Demographic segmentation based on education level. Eduwisata's main target is the community around Sukabumi, with educational tourism programs targeting student groups and families. However, this targeting is still limited to local areas and there has been no significant expansion to further regions or wider market segments. Eduwisata Indo Natural Farm positions itself as an educational tourism destination that offers educational programs in the fields of organic farming and animal husbandry, with a practical educational approach for visitors.